2012
DOI: 10.1017/s0950268812002555
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variability and the transmission of haemorrhagic fever with renal syndrome in Changsha, People's Republic of China

Abstract: The transmission of haemorrhagic fever with renal syndrome (HFRS) is influenced by climatic, reservoir and environmental variables. The epidemiology of the disease was studied over a 6-year period in Changsha. Variables relating to climate, environment, rodent host distribution and disease occurrence were collected monthly and analysed using a time-series adjusted Poisson regression model. It was found that the density of the rodent host and multivariate El Niño Southern Oscillation index had the greatest effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…Our results were consistent with previous studies in India that rice fields are stable ecosystems and sudden increases in mosquito populations as a resultant of climate are uncommon (Das et al, 2006). Absolute humidity, rather than relative humidity was used in this study (Shaman and Kohn, 2009;Xiao et al, 2013b), as absolute humidity is the actual water vapor content of air irrespective of temperature (Xiao et al, 2013a). The absolute humidity is found to be a key factor to affect JEV transmission.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were consistent with previous studies in India that rice fields are stable ecosystems and sudden increases in mosquito populations as a resultant of climate are uncommon (Das et al, 2006). Absolute humidity, rather than relative humidity was used in this study (Shaman and Kohn, 2009;Xiao et al, 2013b), as absolute humidity is the actual water vapor content of air irrespective of temperature (Xiao et al, 2013a). The absolute humidity is found to be a key factor to affect JEV transmission.…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, very few studies have used analytical methods to describe the space-time HFRS spread in Heilongjiang province. On the other hand, the associations between HFRS incidence and climate factors have been always assessed in terms of numerical modeling, for example, autoregressive integrated moving average models (ARIMA), seasonal ARIMA (SARIMA), ecological niche models (ENM), Poisson regression models, multiple regression, conditional logistic regression, and principal components regression (PCR) models [25,34,[45][46][47][48]. Interestingly, none of these studies explored the association between HFRS incidence and climatic factors in the context of their co-variation.…”
Section: Discussionmentioning
confidence: 99%
“…Land surface temperature directly influences the distribution and abundance of A. agrarius populations, 27 whereas ambient temperature considers impacts on both mice and human behaviour. Associations between temperature and HFRS incidence were both positive 11,15,18,21,[25][26][27][28] and negative. 7 Also found was an association between temperature and rodent density 11,12 but no significant association with incidence.…”
Section: Temperaturementioning
confidence: 99%
“…3,11,15,[27][28][29] Liu et al (2006) identified that relative humidity was an important factor in all four seasons. 26 The highest incidence of disease was reported to be in semi-humid areas 8 or in mountainous regions with a humid or semi-humid climate.…”
Section: Humiditymentioning
confidence: 99%
See 1 more Smart Citation